2011
DOI: 10.4081/ejh.2011.e10
|View full text |Cite
|
Sign up to set email alerts
|

The expression of Sirtuins 1 and 4 in peripheral blood leukocytes from patients with type 2 diabetes

Abstract: This study was designed to investigate the relationship between SIRTs 1 and 4 in peripheral blood leukocytes (PBLs) and human type 2 diabetes mellitus (T2DM). SIRTs 1 and 4 have been confirmed to be associated with homeostasis of glucose/lipid metabolism, but their roles in T2DM are still poorly understood. Peripheral blood and biochemical data were collected from 52 healthy individuals (normal control group, NC group) and 113 cases of T2DM patients. Immunocytochemical staining was used to detect SIRT1 and SIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 18 publications
2
26
2
Order By: Relevance
“…2d). Previous studies showed that Sirt1 expression in blood cells is involved in diseases associated with systemic chronic inflammatory processes such as coronary artery disease, type 2 diabetes [35, 36]. Moreover, Mody et al, reported that decreased Sirt1 expression in pulmonary leukocyte was associated with the development of bronchopulmonary dysplasia [37].…”
Section: Discussionmentioning
confidence: 99%
“…2d). Previous studies showed that Sirt1 expression in blood cells is involved in diseases associated with systemic chronic inflammatory processes such as coronary artery disease, type 2 diabetes [35, 36]. Moreover, Mody et al, reported that decreased Sirt1 expression in pulmonary leukocyte was associated with the development of bronchopulmonary dysplasia [37].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from obesity, glucose metabolism is another factor which might influence Sirt4. Evidence has been provided that mRNA expression of Sirt4 in granulocytes and monocytes of T2DM patients was lower compared with healthy individuals, with a negative correlation between Sirt4 and fasting plasma glucose [12]. However, after adjusting for insulin, Sirt4 still remained significantly correlated with BMI, peak GH and IGF-1 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Sirtuin 1 and Sirtuin 4 (Sirt4) are involved in insulin secretion [11] and in maintaining the balance of glucose/lipid metabolism in type 2 diabetes mellitus (T2DM) [12]. Sirt4, ubiquitously expressed in many organs including skeletal muscle and the liver, functions within the mitochondria as negative regulator of mitochondrial oxidative capacity [13].…”
Section: Introductionmentioning
confidence: 99%
“…SIRT1 is a nuclear NAD + -dependent class III histone deacetylase that may regulate cell aging, life span and energy metabolism (13) by engaging in the reciprocal co-regulation of different binding partners (14). SIRT1 is able to adjust the deacetylase activity of various transcription factors that control metabolic and endocrine signals and is widely involved in regulating the mammalian cell life span, INS secretion and glucose/lipid metabolism (15). Genetic variation in the SIRT1 gene is associated with INS resistance and may explain the increased risk of T2DM in the Chinese Han population (16).…”
Section: Introductionmentioning
confidence: 99%